Legal Certainty Regarding Tax Payment Obligations On Shares In Tax Court Decision Number PUT-002784.25/2019/PP/M.XB - Nurzamzany, Aditya Bangkit; Suprapti, Endang (Journal of Law, Politic and Humanities, 2026)
A Limited Liability Company (Perseroan Terbatas or PT) is a legal entity that plays an important role in economic activities, including share ownership arrangements that may involve nominee mechanisms. The use of nominees gives rise to legal and tax issues, particularly in determining the party who is actually responsible for tax obligations, namely between the formal shareholder and the party who substantively enjoys the economic benefits (beneficial owner). The distinction between formal and substantive ownership may result in tax disputes and legal uncertainty, as reflected in Tax Court Decision Number PUT-002784.25/2019/PP/M.XB concerning an Income Tax dispute related to share ownership, in which the tax authority imposed tax liability based on formal ownership, while the appellant denied being the party that received the economic benefits. This study employs a normative juridical method using statutory, doctrinal, and case law approaches. The results indicate that the determination of tax liability must be based on the principle of substance over form by prioritizing economic substance over formal legal structure. The Tax Court’s decision underscores the importance of proving substantive ownership in determining tax obligations and the necessity of clear regulations on nominee arrangements and beneficial ownership to ensure legal certainty, transparency, and tax compliance.